Prospects and Challenges: Driving Sustainable Growth in Azerbaijan through Green Energy - Fataliyeva, Fatima; Alakbarova, Shafiga; Mammadov, Vagif (ADA University, 2023)
This research work aims to investigate policy options to facilitate the transition to green energy in Azerbaijan. Country, being the exporter of fossil fuels, also largely consumes conventional energy sources. However, adverse effects of fossil fuels on environment and public health, as well as exposure to volatility in energy prices in global markets and international commitment to reduce greenhouse emissions as part of the Paris Agreement and Sustainable Development Goals, encourage Azerbaijani government to introduce state policies to increase the stake of renewable energy in local energy mix. In spite of government’s willingness to make transition to green energy, there is slow progress in this area as conventional energy constitutes largest portion in local energy consumption. In this context, government should critically assess obstacles which delay transition to renewables. Moreover, since investment is crucial to implement green energy projects, government should clearly identify financial and legal incentives to promote such projects for foreign and local investors. Therefore, this paper firstly assesses Azerbaijan’s potential for renewable energy and concludes that country holds considerable resources. Afterwards, paper relies on analysis of existing literature to identify obstacles and reveals that lack of trained professionals and public support, along with shortage of investment from local and foreign businesses slow down development of green energy sector in Azerbaijan. These findings are later confirmed with survey which gathered 70 respondents. Paper then moves to analysis of each obstacle and utilizes information from interviews with experts to devise policy solutions for each challenge. It is found that training, financial incentives in the form of tax exemptions and subsidies, public awareness campaigns, and well-developed legislative framework are required to attract and protect investment and secure public support.
Keywords: Renewable energy sources -- Azerbaijan; Energy policy -- Azerbaijan; Sustainable development -- Energy aspects; Public and International Affairs